Perspektif Hukum Islam terhadap Adat Istiadat Mogama’ di Kelurahan Mogolaing: Perbedaan Nilai dengan Ajaran Islam - Suleman, Frangky; Soleman, Moh. Rafiq; Ontowirjo, Nurul Izzah Assyifa (IAIN Manado, 2023)
This research aims to analyze the Islamic perspective on implementing the Mogama’ customary practices in Mogolaing Village, West Kotamobagu. A qualitative method was employed, conducting field research in Mogolaing Village, gathering data through observation, interviews, and documentation, which were analyzed based on information from the village head, customary leaders, religious figures, and community leaders. The research findings reveal differences in values between the Islamic interpretation and the practice of Mogama’ and Islamic law. Islamic teachings, such as respect for women, friendship, cooperation, blessings through congregational prayers, good treatment of women, and the development of strong familial ties, are not aligned with the values in Mogama’s practices. Some scholars discuss 'urf related to customs and traditions, utilizing 'urf and customs/practices appropriate to their context for adaptation. However, the traditional marriage procession of Bolaang Mongondow is considered in line with Islamic teachings as